Artificial insemination, a relief for DR Congo’s cattle keepers - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2024)
Bulls have long been more a bane than blessing for cattle breeding in DR Congo due to multiple factors: difficulty in accessing a bull, inbreeding, and disease transmission. Artificial insemination is the cover-all solution. AID-I GLR partner Vétérinaires Sans Frontières (VSF) has acquired veterinary imaging machine (VIM) devices that allow for precise insemination, and ultrasound machines that enable inseminators to analyse insemination results within two to four weeks. Importantly, these advanced tools will be accessible to farmers.